Age Differences in Vestibular Brain Connectivity Are Associated With Balance Performance - Noohi, Fatemeh; Kinnaird, Catherine; De Dios, Yiri; Kofman, Igor S.; Wood, Scott J.; Bloomberg, Jacob; Mulavara, Ajitkumar; Sienko, Kathleen H.; Polk, Thad A.; Seidler, Rachael D. (Frontiers in Aging Neuroscience, 2020)
Visual and auditory brain network connectivity decline with age, but less is known about age effects on vestibular functional connectivity and its association with behavior. We assessed age differences in the connectivity of the vestibular cortex with other sensory brain regions, both during rest and during vestibular stimulation. We then assessed the relationship between vestibular connectivity and postural stability. The results showed a main effect of age and condition, suggesting that vestibular connectivity was higher in young adults than older adults, and vestibular connectivity increased from resting state to stimulation trials. Surprisingly, young adults who exhibited higher connectivity during stimulation also had greater body sway. This suggests that young adults who exhibit better balance are those who respond more selectively to vestibular inputs. This correlation is non-significant in older adults, suggesting that the relationship between vestibular functional connectivity and postural stability differs with age.